On the Requirements of Legal Justice of the Administrative Law Enforcement Activity - S. V. Yarkovoy (Сибирское юридическое обозрение, 2019)
The article considers issues of understanding by the administrative-legal science of legal justice of the law-enforcement activity of executive authorities, other public administration bodies. The Author defines the concept and highlights the requirements of legal justice of administrative law enforcement, draws a correlation of these requirements with the requirements of legality, validity, appropriateness of this activity.